Hysteria as an Escape for the Female Character in â€œIleâ€ by Eugene Oâ€™Neill - Nestiani Hutami (Tell : Teaching of English Language and Literature Journal, 2020)
Hysteria or female madness occurs mostly in women. It happens because according to research the health condition of women is worse than men, significantly related to a mental condition. Women are more likely to have unexpressed desires that lead to stress and develop depression when faced with the reality that does not match their expectations. To understand more about hysteria, this study attempts to examine the symptoms of hysterical behaviors that occur on the female character, Mrs. Keeney, in a play entitled â€œIleâ€ written by Eugene Oâ€™Neill. This is qualitative research in which the data were in the form of dialogues between the characters, especially related to Mrs. Keeney. The results of this study show that the symptoms of hysterical behaviors gradually appear, from mild to severe symptoms. In addition, they occur mostly because the female character is unable to face the harsh reality that is incompatible with her expectation, and thus she prefers to escape from it.